Effect of Addition Bali Orange Peel Pectins on The Mechanical Properties of Garut Starch Bioplastic - Sholekhahwati Sholekhahwati; Endaruji Sedyadi (Gontor AGROTECH Science Journal, 2020)
Research has been conducted on the effect of adding grapefruit peel pectin on the physical properties of glycerol plasticized arrowroot starch bioplastic. This study aims to determine the effect of adding grapefruit peel pectin to its mechanical properties including thickness, tensile strength, elongation, and modulus young. Variations of grapefruit peel pectin used were 0, 1, 2, 3, 4, and 5 g. Bioplastics are made using hot blending methods. The results showed that the addition of grapefruit pectin could increase the thickness value, decrease the tensile strength value, increase the elongation value, and decrease the young modulus. The optimum results obtained are with a thickness value of 0.156 mm, a tensile strength value of 3.9882 MPa, an elongation value of 10.5499%, and a modulus young value of 0.3765 MPa. Overall, it can be concluded that the addition of grapefruit peel pectin has a significant effect on the mechanical properties of glycerol plasticized arrowroot starch bioplastic.